Assessment of Nurses Knowledge Toward Neonate with Birth Asphyxia at Neonatal Intensive Care Unit in Pediatric Hospitals at Babylon Governorate (Medico Legal Update, 2020)
Background: Birth asphyxia is neonates’ inability to activate and sustain breathing at conception .. It is alsorecognized as a condition that arises when blood gas delivery is compromised, contributing to hypoxemiaand hypercapnia The combination of hypoxia and ischemia may contribute to a cascade of biochemicalchanges in the body contributing to neuronal brain loss and brain harmObjectives: In order the aim of study to Identify the demographic characteristic of sample , Identifyknowledge of nurses in caring of neonate with birth asphyxia at NICU at pediatric hospitals in Babylongovernorate , determine the relationship between nurses knowledge with birth asphyxia at NICU with certainof socio- demographic characteristics of sample Babylon, Iraq.Methodology: A comprehensive research is undertaken to investigate nurses’ understanding of Neonatewith Birth Asphyxia in the Neonatal Intensive Care Unit at Babylon Governorate Pediatric Hospitals Arandomized random sample of (62) nurse is chosen with the usage of the chance sampling method. Theresearch group is spread in the Neonatal Intensive Care Unit at Babylon Governorate Pediatric Hospitals.The data was obtained using a built-in self-report questionnaire and evaluated using the concise statisticalanalysis method that involves “frequencies & percentages” and the Inferential statistical data analysismethodology used for the Chi-square test.Results: Results of the analysis show that the participants with excellent awareness served (66.1 percent),whereas those with bad information (33.9 percent) reflected nurses in the Neonatal Intensive Care Unit atthe Babylon Governorate Pediatric Hospitals. In comparison, the mean age of experienced nurses is 32.73± 9.33 while those with bad awareness are 26.05 ± 5.86. Significant linkages exist between Education andawareness engagement, p = 0.015.Conclusions and recommendations : Around 66 per cent of nurses have experience of birth asphyxia, thestudy showed. Despite Born Asphyxia, about half of them have strong and optimistic disposition towardsNeonate. Education will be deemed to improve nurses’ awareness of Neonate with Birth Asphyxia